2019
DOI: 10.1002/htj.21532
|View full text |Cite
|
Sign up to set email alerts
|

The hydraulic‐thermal performance of miniature compact heat sinks using SiO2‐water nanofluids

Abstract: Ever since the rapid increase in both the demand for the miniature electronic devices and their applications, heat dissipation in the electronic components has been a serious issue. A miniature plate‐pin heat sink model with square, circular, and elliptic pins is considered to enhance the hydrothermal performance of this kind of compact heat sink (CHS). Water and 3% of SiO2‐water nanofluids of volume fraction were used with different Reynolds number ranges (100‐1000). The findings show that the base temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The most considerable value of dissipation rate is for SiO 2 –H 2 O nanofluids nearly 25% greater than pure water for different pumping power because the thermal conductivity of SiO 2 ‐water and the mass flow rate are higher than that of pure water and other nanofluid types (Brownian motion). This finding is confirmed with the numerical results of Fadhil et al and experimental data of Zirakzadeh et al…”
Section: Resultssupporting
confidence: 88%
“…The most considerable value of dissipation rate is for SiO 2 –H 2 O nanofluids nearly 25% greater than pure water for different pumping power because the thermal conductivity of SiO 2 ‐water and the mass flow rate are higher than that of pure water and other nanofluid types (Brownian motion). This finding is confirmed with the numerical results of Fadhil et al and experimental data of Zirakzadeh et al…”
Section: Resultssupporting
confidence: 88%
“…The thermal fluids have recommendable thermal properties; such nanofluids which have particularly favorable thermal conductivity compared with other base coolant fluids as oil, water, glycerine, etc. Since the thermohydraulic characteristics of nanofluids are worthy, therefore, different sorts of nanofluids are applied in many engineering applications—traditional and compact HSs, solar energy, heat pipes, thermal energy storage, and free and forced convection . However, these applications using nanofluids have some limitations that cannot be neglected.…”
Section: Introductionmentioning
confidence: 99%
“…If the value of NUR greater than 1 indicated that the heat transfer rate is enhanced on that fluid, whereas reduction of heat transfer is indicated when NUR is less than 1 (Fadhil et al , 2019). The present study was conducted for both the constant heat flux ( " = 10,000 W/m 2 ) and constant wall temperature (Tw = 313.15 K) boundary conditions.…”
Section: Numerical Implementationmentioning
confidence: 99%